Implementation and usefulness of outcomes-based instruction among college of education students - Martin, Matronillo M. (Asian Journal of Assessment in Teaching and Learning, 2019)
This study aimed to determine the status of implementation of Outcomes-based instruction as mode of instruction employed by the instructors in terms of practices and environment and its level of usefulness in terms of academic, attitude and instruction as perceived by the College of Education students of Ifugao State University Potia Campus. This study used a descriptive method of research. Based on the results, Outcomes-based instruction was implemented in terms of practices and environment. The respondents assessed that it was useful in terms of academic and instruction. On the other hand, it was very useful in terms of attitudes. Based from the findings, if outcomes-based instruction was implemented, it was also useful. This indicated that there was a significant relationship between the implementation and usefulness of OBE with the r-value 0.69. An action plan was presented to address the indicators which obtained the least weighted mean in each aspect. The researcher recommends that both the faculty members and the students should have an extensive seminars and orientations about Outcomes-based instruction. Furthermore, conduct a continuous monitoring on its implementation and usefulness for further improvements. Also, the college shall conduct related activities which integrate a broader context of Outcomes-Based Instruction for the enhancement of the students’ skills.